Nuclear import and dimerization of tomato ASR1, a water stress-inducible protein exclusive to plants - Ricardi, M.M. (2012)
The ASR (for ABA/water stress/ripening) protein family, first described in tomato as nuclear and involved in adaptation to dry climates, is widespread in the plant kingdom, including crops of high agronomic relevance. We show both nuclear and cytosolic localization for ASR1 (the most studied member of the family) in histological plant samples by immunodetection, typically found in small proteins readily diffusing through nuclear pores. Indeed, a nuclear localization was expected based on sorting prediction software, which also highlight a monopartite nuclear localization signal (NLS) in the primary sequence. However, here we prove that such an "NLS" of ASR1 from tomato is dispensable and non-functional, being the transport of the protein to the nucleus due to simple diffusion across nuclear pores. We attribute such a targeting deficiency to the misplacing in that cryptic NLS of two conserved contiguous lysine residues. Based on previous in vitro experiments regarding quaternary structure, we also carried out live cell imaging assays through confocal microscopy to explore dimer formation in planta. We found homodimers in both the cytosol and the nucleus and demonstrated that assembly of both subunits together can occur in the cytosol, giving rise to translocation of preformed dimers. The presence of dimers was further corroborated by means of in vivo crosslinking of nuclei followed by SDS-PAGE. © 2012 Ricardi et al.